Management of proximal rectus femoris injuries – do we know what we’re doing?: A systematic review - Bogwasi, Lone; Holtzhausen, Louis; Janse van Rensburg, Dina; Jansen van Rensburg, Audrey; Botha, Tanita (Biology of Sport, 2023)
Rectus femoris (RF) injury is a concern in sports. The management RF strains/tears and avulsion injuries need to be clearly outlined. A systematic review of literature on current management strategies for RF injuries, and to ascertain the efficacy thereof by the return to sport (RTS) time and re-injury rates. Literature search using Medline via PubMed, WorldCat, EMBASE, SPORTDiscus. Eligible studies were reviewed. Thirty-eight studies involving hundred and fifty-two participants were included. Majority (n = 138; 91%) were males, 80% (n = 121) sustained RF injury from kicking and 20% (n = 31) during sprinting. The myotendinous (MT), (n = 27); free tendon (FT), (n = 34), and anterior-inferior iliac spine (AIIS), (n = 91) were involved. Treatment was conservative (n = 115) or surgical (n = 37) across the subgroups. 73% (n = 27) of surgical treatments followed failed conservative treatment. The mean RTS was shorter with successful conservative treatment (MT: 1, FT: 4, AIIS avulsion: 2.9 months). Surgical RTS ranged from 2–9 months and 18 months with labral involvement. With either group, there was no re-injury within 24 months follow-up. With low certainty of evidence RF injury occurs mostly from kicking, resulting in a tear or avulsion at the FT and AIIS regions with or without a labral tear. With low certainty, findings suggest that successful conservative treatment provides a shortened RTS. Surgical treatment remains an option for failed conservative treatment of RF injuries across all subgroups. High-level studies are recommended to improve the evidence base for the treatment of this significant injury